The African Religious Landscape : an examination of Shona traditional beliefs and practices in light of HIV and AIDS, and its ramifications for mitigation and care - Groenewald, Alphonso, 1969- (University of Pretoria, 2018)
Thesis (PhD)--University of Pretoria, 2017.